TRAINING ON MAKING PAVING BLOCKS FROM CONCRETE WASTE TO IMPROVE THE ECONOMY - Rajib Muammar; Rina Purnama Sari; Saiful Bahri; Iqbal; Fauziansyah (Jurnal Pengabdian Bangsa, 2025)
This study aims to improve community skills in processing concrete waste into products with economic value, especially paving blocks, through training activities. Concrete waste which is generally considered useless and polluting the environment, is reprocessed into useful construction materials. The implementation method includes initial observation, training planning, activity implementation, and evaluation of results. Training activities are carried out with a participatory approach, involving the community directly in the process of mixing materials, molding, and drying paving blocks. The results of the study showed that this training succeeded in increasing the knowledge and skills of participants in producing paving blocks from concrete waste. In addition, participants began to see the potential for micro-businesses that could be developed from the results of this training. Economically, this activity opens up new opportunities to increase community income, especially in areas with high unemployment rates and limited access to formal employment. In conclusion, training in making paving blocks from concrete waste has proven effective as an innovative solution in waste management as well as a strategy for empowering the community's economy. It is hoped that this activity can be replicated in other areas as a sustainable effort to create a clean environment and an independent economy.